2010
DOI: 10.1128/jcm.02243-09
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting Pneumococcal Carriage by Use of Broth Enrichment and PCR Techniques for Enhanced Detection of Carriage and Serotypes

Abstract: The measurement of pneumococcal carriage in the nasopharyngeal reservoir is subject to potential confounders that include low-density and multiple-strain colonization. To compare different methodologies, we picked a random sampling of 100 nasopharyngeal specimens recovered from infants less than 2 years of age who were previously assessed for pneumococcal carriage and serotypes by a conventional method that used direct plating from the transport/storage medium (50 specimens were culture negative and 50 specime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
194
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 241 publications
(206 citation statements)
references
References 17 publications
10
194
1
1
Order By: Relevance
“…While other studies have used oligonucleotide permutations to account for geographical differences in S. pneumoniae serotype distribution (USA, Latin America, Africa, and Asia), [17,24,40] this study showed that oligonucleotides permutations did not affect the performance characteristics of PCR-based serotyping. This study does not preclude additional validation if different permutations are used, or use of ongoing quality assurance controls.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…While other studies have used oligonucleotide permutations to account for geographical differences in S. pneumoniae serotype distribution (USA, Latin America, Africa, and Asia), [17,24,40] this study showed that oligonucleotides permutations did not affect the performance characteristics of PCR-based serotyping. This study does not preclude additional validation if different permutations are used, or use of ongoing quality assurance controls.…”
Section: Discussionmentioning
confidence: 79%
“…[16][17][18][19][20][21][22][23][24][25][26][27][28] Since cmPCR have a limited number of serotypes in each PCR reaction, they have been designed to target the most prevalent serotypes causing IPD, often in sequential reactions. [21][22][23][24][25][26] However, sequential PCR may not be the most cost effective strategy to identify S. pneumo-niae serotypes that are vaccine-preventable. This study used oligonucleotide permutations in a modified set of cmPCR reactions (termed cmPCRmod) to reduce the amount of testing required to identify S. pneumoniae serotypes covered by the PCV7, PCV13, or PPV23 vaccines.…”
Section: Introductionmentioning
confidence: 99%
“…Multiplex PCRs, microarrays, and latex agglutination assays have been used to detect multiple serotypes in colonization, with different success rates (23)(24)(25). The use of culture for detection of multiple serotypes is limited by the number of colonies that need to be identified in order to have a realistic probability of identifying a minor serotype (26,27).…”
Section: Ip Et Almentioning
confidence: 99%
“…After boiling for 10 minutes, cell debris was pelleted by centrifugation (13.000 x g for 2 minutes) and the supernatant was used for the PCR. The multiplex PCR was performed using the primers of the published protocol of Pai et al [7], adapting the primer set as proposed by Carvalho et al [8]. Because the CDC protocol detects 16 serotypes/groups which have never been reported from patients with invasive pneumococcal disease or in carriage studies in Venezuela, these serotypes were excluded from the typing scheme.…”
Section: Multiplex Pcr Assaymentioning
confidence: 99%
“…Ongoing research, especially nasopharynx carriage studies, carried out in the last 10 years in our country to increase the knowledge of pneumococcal epidemiology, has demonstrated a need for a faster and cheaper technique for serotyping. Here, we evaluate for future investigational use a serial multiplex PCR (mPCR) approach, based on one originally developed by Pai et al [7] [8]). For the PCR detection of strains from Venezuela, we adapted this multiplex PCR scheme by modifying the order of the reactions and moving serotypes into different reaction mixtures from where they were previously, based on the prevalence data of invasive pneumococcal serotypes/groups in Venezuela.…”
Section: Introductionmentioning
confidence: 99%